Problems and concerns with the 2022 South African census - Moultrie, Tom A; Dorrington, Rob E (South African Journal of Science, 2024)
A census provides a snapshot of a population at a point in time. In addition to describing the basic demographic and socio-economic characteristics of a population, census data provide denominators for estimating rates; inform resource allocation and policy, development and infrastructural investment; and are used to define sampling frames for other national inquiries. Although the 2022 South African census attempted to correct for a national undercount of over 30%, it was not entirely successful. We identify a number of concerns with the estimates released, which suggest that the data may not be fit for purpose.